2015
DOI: 10.1007/s00726-015-1915-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homoarginine, arginine, asymmetric dimethylarginine and total homocysteine interrelationships in rheumatoid arthritis, coronary artery disease and peripheral artery occlusion disease

Abstract: Elevated circulating concentrations of total L-homocysteine (thCys) and free asymmetric dimethylarginine (ADMA) are long-established cardiovascular risk factors. Low circulating L-homoarginine (hArg) concentrations were recently found to be associated with increased cardiovascular morbidity and mortality. The biochemical pathways of these amino acids overlap and share the same cofactor S-adenosylmethionine (SAM). In the present study, we investigated potential associations between hArg, L-arginine (Arg), ADMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…For North America and Australia, the rate is 8%-20%. The TT rate in Japan is 12% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)24). The results of this study are in compliance with the frequency reported in white Turkish population.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For North America and Australia, the rate is 8%-20%. The TT rate in Japan is 12% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)24). The results of this study are in compliance with the frequency reported in white Turkish population.…”
Section: Discussionsupporting
confidence: 86%
“…In severe MTHFR deficiency, hyperhomocysteinemia and homocysteinuria occur (12). Hyperhomocysteinemia is a risk factor for coronary heart, peripheral, vascular, and cerebrovascular disease (10)(11)(12)(13)(14). Recent studies reported an increased plasma Hcy levels in patients with chronic periodontitis (15).…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study confirm the findings of previous studies, which report an elevation or a significant increase in plasma Hcy concentration. Many studies have also shown that the level of Hcy is significantly elevated in patients with RA compared with the level of Hcy in healthy subjects (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In RA, this could be beneficial since elevated plasma homocysteine has been associated with increased risk of cardiovascular diseases. 27 …”
Section: Discussionmentioning
confidence: 99%